Acetabular Protrusion in a Cohort of Patients with Osteogenesis Imperfecta Evaluated in a Pediatric Hospital - Ramos-Mejía, Rosario; Monterroza-Quintana, Francisco; Primomo, Claudio; Goyeneche, Rodolfo; Fano, Virginia (Journal of Pediatric Genetics, 2021)
Acetabular protrusion (AP) is present in 33 to 55% of patients with osteogenesis imperfecta (OI). Even though the finding is relatively common, it is poorly described in pediatric patients. The objective of this study was to describe the incidence and associations of AP in pediatric OI patients. We retrospectively and cross-sectionally evaluated clinical histories and radiographic findings of OI patients aged 2 to 19.5 years, recording sex, age, severity, anthropometric measurements, ambulation status, femoral fractures history, and occurrence of orthopaedic surgeries and nephropathy. AP was considered present when the center-edge (CE) angle was more than 35 degrees and the acetabular line crossed the Kohler's line by more than 1 and 3 mm in boys and girls, respectively, and 3 and 6 mm in adult males and females, respectively. The association with risk factors and complications was analyzed through univariate and multivariate logistic regression. A total of 71 children were evaluated. The median age was 8.6 years, and 54.9% of them had moderate to severe forms of OI. In 71.8% of the children, an abnormal CE angle was found, being frequent in mild, moderate, and severe cases. AP was present in 22.5% of all patients and in 41% of children with moderate to severe OI, and was significantly associated with older ages (p = 0.0062) and nonwalking status (p = 0.0093). We found a high prevalence of AP in children with moderate to severe forms of OI, which was present even at younger ages. In addition, we found a significant increase in the number of children with abnormal CE angles even in those with mild forms of OI. The presence of AP was associated with the severity of the OI and age, and in a negative association with the ambulatory status.
Keywords: acetabular protrusion; osteogenesis imperfecta; pediatric